(untitled) (Research, Society and Development, 2020)
The pressure exerted on the Cerrado due to forest fragmentation has caused concern about the regenerative capacity of these areas. Riparian forest areas, due to their proximity to the watercourse, are conservation priorities and often have disturbed fragments. In this sense, the objective of this study was to evaluate the natural regeneration potential of a stream with its disturbed riparian forest, surrounded by pastures. The method chosen for plot demarcation was simple random, consisting of 6 plots of 10 m x 15 m. We carried out the forest inventory inside each plot, inserting all the trees that had a breast height circumference greater than or equal to 15 cm. We sampled 63 individuals belonging to 10 families, distributed in 18 different species. The largest representativeness is present in the Fabaceae family. Regarding the ecological group, 61% corresponded to pioneer species, 33% to secondary species and only one species was classified as climax species. Regarding the Shannon-Weaver index, it presented low floristic diversity (1.67 individual-individuals). The two species with the highest importance value index were the yellow ipê (Tabebuia ochracea) and pau terra (Qualea grandiflora), secondary species with values of 65.87 and 41.44 respectively. Disturbed riparian forest indicates a slow and incipient recovery process mainly in open areas and near borders. The studied area has potential for natural regeneration and proximity to good quality fragments, but it is necessary to plant enrichment with secondary forest species in order to accelerate the recovery process.